2010
DOI: 10.1172/jci40124
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid promotes an acute inflammatory response to sterile cell death in mice

Abstract: Necrosis stimulates inflammation, and this response is medically relevant because it contributes to the pathogenesis of a number of diseases. It is thought that necrosis stimulates inflammation because dying cells release proinflammatory molecules that are recognized by the immune system. However, relatively little is known about the molecular identity of these molecules and their contribution to responses in vivo. Here, we investigated the role of uric acid in the inflammatory response to necrotic cells in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
246
1
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(264 citation statements)
references
References 32 publications
10
246
1
7
Order By: Relevance
“…1E). Striatal urate was also significantly lower in the Tg mice (P < 0.05, t test) but to a lesser extent than in serum despite broad expression of UOx transgene driven by a β-actin promoter (10) (Fig. 1F).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…1E). Striatal urate was also significantly lower in the Tg mice (P < 0.05, t test) but to a lesser extent than in serum despite broad expression of UOx transgene driven by a β-actin promoter (10) (Fig. 1F).…”
Section: Resultsmentioning
confidence: 92%
“…UOx Tg mice were obtained from Kenneth L. Rock, Department of Immunology, University of Massachusetts, Worcester, MA. UOx transgene expression is driven by a strong constitutive (β-actin) promoter (10). Hemizygous UOx Tg mice were used.…”
Section: Methodsmentioning
confidence: 99%
“…Several DAMPs can be released or generated into the extracellular environment by dying cells or in relation to abnormal metabolism, and then trigger sterile inflammation, including proteins like: i) high-mobility group box 1 (HMGB1) [102], ii) heat shock proteins (HSPs) [103], iii) proteins of extracellular matrix generated following tissue injury (i.e., hyaluronan, heparin sulfate and biglycan) as modified/cleaved by enzymes released from dying cells or by other proteases [104,105]. Non-protein DAMPs such as ATP and uric acid (that) can be released or generated during cell injury and death [106]; mitochondria are a rich source of DAMPs like, in addition to ATP, mitochondrial DNA, formyl peptides and cytochrome C [107] which are effective stimulators of inflammation. Along these lines, inflammasomes represent a group of protein complexes able to recognize PAMPs and DAMPs and that control activation of the proteolytic enzyme caspase-1, which in turn regulates maturation of the pro-inflammatory cytokines IL-1β and IL-18 [108,109].…”
Section: Inflammasomes and Liver Fibrogenesismentioning
confidence: 99%
“…We used the TLR agonists poly I:C and LPS, as well as BCG and Mycobacterium smegmatis as examples of natural, complex sources of multiple PAMPs. Monosodium urate crystals (MSU), which are stable danger signals with well-defined proinflammatory activity (19), were selected because of their prominent role in tumor rejection and the antitumor response to chemotherapy (20,21). We found that only some of these treatments were able to delay primary tumor growth, reduce metastatic load, and activate both CD8 + T cells and NK cells.…”
mentioning
confidence: 99%